2013
DOI: 10.1016/j.jenvman.2013.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical–biological treatment: Performance and potentials. An LCA of 8 MBT plants including waste characterization

Abstract: In the endeavour of avoiding presence of biodegradable waste in landfills and increasing recycling, mechanical-biological treatment (MBT) plants have seen a significant increase in number and capacity in the last two decades. The aim of these plants is separating and stabilizing the quickly biodegradable fraction of the waste as well as recovering recyclables from mixed waste streams. In this study the environmental performance of eight MBT-based waste management scenarios in Spain was assessed by means of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 38 publications
0
55
0
Order By: Relevance
“…Güereka et al (2006), in the case of biowaste management in Barcelona (Spain), find that as a result of producing electricity, biogas production and incineration are the processes that most contribute to reducing impact. Montejo et al (2013) analyze different mechanical biological treatment (MBT) plants in Castile and León (Spain). Their results showed that performance is strongly linked to energy and materials recovery efficiency.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Güereka et al (2006), in the case of biowaste management in Barcelona (Spain), find that as a result of producing electricity, biogas production and incineration are the processes that most contribute to reducing impact. Montejo et al (2013) analyze different mechanical biological treatment (MBT) plants in Castile and León (Spain). Their results showed that performance is strongly linked to energy and materials recovery efficiency.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In fact, numerous studies have been published in recent years in which this tool is applied in the environmental assessment of different scenarios of municipal waste management in different countries, such as Italy (Arena et al, 2003;Cherubini et al, 2009;Blengini et al, 2012), Spain (Güereka et al, 2006;Bovea and Powell, 2006;Montejo et al, 2013), Lithuania (Miliūte and Staniškis, 2009), Brazil (Mendes et al, 2004), Canada (Assamoi and Lawryshyn, 2012), the United States (Vergara et al, …”
Section: Introductionmentioning
confidence: 99%
“…The environmental assessment followed the principles of consequential life cycle assessment (28,29). The functional unit was "treatment of 1 tonne (1 t = 1 Mg, wet weight) of municipal solid waste (MSW)".…”
Section: Scope and Functional Unitmentioning
confidence: 99%
“…Electricity, heat, and transport fuel (produced from waste incineration or biogas conversion) were assumed to substitute marginal peak-load electricity, district heating, and transport fuel production following the principles of consequential LCA (28,29). For fossil fuels used for electricity and district heating production, coal and natural gas represented two ends of the interval with respect to CO 2 emissions per fuel energy unit.…”
Section: Energy Systemmentioning
confidence: 99%
See 1 more Smart Citation